2018
DOI: 10.1111/1750-3841.14321
|View full text |Cite
|
Sign up to set email alerts
|

Meat Color Stability of Ovine Muscles Is Related to Glycolytic Dehydrogenase Activities

Abstract: The relationship between glycolytic dehydrogenase, including glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), lactic dehydrogenase (LDH), and meat color stability was studied in this study using ovine muscle. Three different ovine muscles, including M. longissimus lumborum (LL), M. semimembranosus (SM), and M. psoas major (PM), were obtained (n = 10, respectively), and then displayed for 7 days at 4 °C. The LL and SM muscle had higher surface redness, higher (P < 0.05) GAPDH activity, nicotinamide adenine din… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Several proteins showed the relationships between their degradation trends and protease activity or meat quality traits, especially meat color and water-holding capacity. In particular, meat color traits were majorly related with the degradation of enzymes responsible for glycolysis, such as glycerol-3-phosphate dehydrogenase, phosphoglucomutase 1, glyceraldehyde-3-phosphate dehydrogenase, and glucose-6-phosphate isomerase as reported in previous study which demonstrate the correlations among glycolytic dehydrogenase including glyceraldehyde-3-phosphate dehydrogenase, lactic dehydrogenase, and meat color stability were observed in ovine muscle (Xin et al, 2018). For water-holding capacity, Joo et al (1999) demonstrated that the rate of drip loss declined according to the increasing of the sarcoplasmic protein solubility.…”
Section: Discussionsupporting
confidence: 71%
“…Several proteins showed the relationships between their degradation trends and protease activity or meat quality traits, especially meat color and water-holding capacity. In particular, meat color traits were majorly related with the degradation of enzymes responsible for glycolysis, such as glycerol-3-phosphate dehydrogenase, phosphoglucomutase 1, glyceraldehyde-3-phosphate dehydrogenase, and glucose-6-phosphate isomerase as reported in previous study which demonstrate the correlations among glycolytic dehydrogenase including glyceraldehyde-3-phosphate dehydrogenase, lactic dehydrogenase, and meat color stability were observed in ovine muscle (Xin et al, 2018). For water-holding capacity, Joo et al (1999) demonstrated that the rate of drip loss declined according to the increasing of the sarcoplasmic protein solubility.…”
Section: Discussionsupporting
confidence: 71%
“…All these three processes require electrons produced from NADH regeneration via lactate dehydrogenase (LDH) or glyceraldehyde 3-phosphate dehydrogenase (GAPDH) activity [9,13]. Metmyoglobin enzymatic reduction that happens in the mitochondrial membrane through cytochrome b5 reductase is considered the most important cellular enzymatic process involved in meat color development because of its critical importance in cellular electron transport [14,15]. The metmyoglobin formed during the oxidation phase is the compound that more strongly affects the meat's color and appearance, and it can ultimately determine the consumer's purchase willingness [16].…”
Section: Introductionmentioning
confidence: 99%
“…The GAPDH enzyme is involved in various metabolic processes such as stress response, cell dysfunction, cytotoxicity, or cell proliferation, making it essential in maintaining homeostasis and regulating cell death, with a constant gene expression (Tristan, Shahani, Sedlak, & Sawa, 2011). Similarly, it may be associated with the maintenance of meat color stability (Xin et al, 2018). In the present study, the expression of the GAPDH gene transcript was the most stable one according to geNorm, Normfinder, and Bestkeeper.…”
Section: Resultsmentioning
confidence: 47%